Methotrexate‐induced pancytopenia: a case series of 46 patients. (5th March 2017) - Ajmani, Sajal; Preet Singh, Yogesh; Prasad, Shiva; Chowdhury, Abhra; Aggarwal, Amita; Lawrence, Able; Misra, Ramnath; Mishra, Richa; Agarwal, Vikas
Abstract: Aim: Methotrexate (MTX) has the potential to cause serious adverse reactions and even mortality. We analyzed the predisposing factors and outcome in patients with MTX‐induced pancytopenia admitted into our unit from 1996 to 2015. Methods: Patients were identified by departmental database search. Pancytopenia was defined as white blood cell count (WBC) < 3500 cells/mm 3, hemoglobin (Hb) < 11 g/dL and platelet count < 150 000 cells/mm 3 . Severe pancytopenia was defined as WBC < 2000 cells/mm 3, Hb < 10 g/dL and platelet count < 50 000 cells/mm 3 . Results: Forty‐six patients were included in the study (female = 35). Twenty‐four had been under the care of either primary care physicians or orthopedic surgeons and presented to us with pancytopenia. Sixteen patients had severe pancytopenia. Disease distribution was as follows: rheumatoid arthritis 33, psoriasis eight, systemic sclerosis two and others three. The median dose of MTX was 10 mg/week and median duration of treatment was 11 months. The median cumulative dose was 750 mg. Symptoms at presentation included: oral mucositis ( n = 37); fever ( n = 24); diarrhea ( n = 12), bleeding gums ( n = 5) and purpura ( n = 3). The potential risk factors were: hypoalbuminemia ( n = 23), renal insufficiency ( n = 14), dosing errors ( n = 13) and non‐supplementation of folates ( n = 7). Thirteen patients died. WBC at admission was found to determine survival ( P < 0.05). Conclusion: In patients on MTX, oral mucositis and fever can herald pancytopenia. MTX‐induced pancytopenia is associated with high mortality. WBC at admission is the most important prognostic factor. There is need for increased awareness among physicians to minimize prescribing errors. A national guideline on monitoring of patients on MTX is desirable.